Ruta de Agroturismo para el cantón Saraguro Provincia de Loja - Pineda Escobar., Pablo Israel (2016)
Ecuador is one of several mega countries in the world, with a high rate of endemism, which retains 18% of its territory as protected areas being eleven great importance worldwide. Not to mention the diversity of peoples and nationalities that bring with them customs, traditions, legends and worldviews that impress at every step. The southern region of Ecuador and especially the province of Loja, also known as the musical and cultural capital of Ecuador, has innumerable natural and cultural tourist attractions which has allowed its cantons to develop projects to increase the influx of tourists to them. Saraguro is one of the main cantons of Loja Province which has great cultural and natural wealth. As Saraguro has great potential tourism, it was important to develop this research. And its general objective was: "Designing the Route of Agroturism for canton Saraguro, province of Loja." .- within this objective everything related to the development of research work is included. To achieve the same three specific objectives were set; "To diagnose the main tourist attractions for the Route of Agroturism of canton Saraguro Province of Loja", for that, it was used the Analytical Method that served to make an analysis of the tourist attractions of the canton Saraguro, which are part of the object of study; The Inductive Method, which was used to analyze the particularities of parishes and communities in economic and socio-cultural aspects; the techniques of direct observation and interview were also applied; In addition, the Diagnostic Matrix of communities of Carla Ricaurte Quijano, Tourist Inventory Sheets of the (MINTUR) and Hierarchy of tourist attractions. The support of the Territorial Planning Plan served as a complement to the collection of information: geographical, tourist, economic, political and social; Finally the SWOT matrix was done to determine the current situation of the canton. The second objective was also to “Elaborate the Route of Agrotourism for Saraguro, province of Loja” The Synthetic Method was used to determine which communities will be integrated into the tourist activity, taking into account the potential they possess , Additionally, the use of the Global Positioning System (GPS) served to carry out the survey of the geographical coordinates of the tourist attractions, as well as times and distances between them; A camera that was used as a digital support, and the matrix for validating tourist routes, designed by the Ministry of Tourism; Also pictograms of the attractions, activities and tourist services were used for the design and elaboration of the map of the route, likewise an identification mark was created using the main elements, finally it was established the name of Ruta AgroturistícaCultivos Milenarios, complemented with the elaboration of the script and itinerary following the established order; The third Objective was also designed .- "To propose strategies on the product: Agrotourism route of canton Saraguro province of Loja" .- for its development it was used the deductive method allowing to establish the conclusions that have been caused based on the problematic; Strategies were also developed for the promotion and dissemination of the route, the first strategy consists of the development of advertising media such as poster and brochures; The second strategy consists on the elaboration of a tourist package for the promotion of the route; For the third strategy a billboard was developed; The fourth strategy consists on the elaboration of souvenirs such as: cloth bag, cap and jug; Finally the fifth strategy is the socialization of the proposal, for this, it was used the MARPP technique consisting of three phases; The first is the call made by an office addressed to the Major of the canton Saraguro, Lic. Abel Sarango, requesting a date for socialization; In the second phase the results of the research work on the development of the Agroturistic Route were presented. Finally, in the third phase, observations were made. The result of the socialization determined that the Route "Agroturistíca Cultivos Milenarios" will contribute to the promotion of agricultural activity as a new tourist alternative for the canton. Finally, the conclusions and recommendations of the thesis work were presented, which are mostly addressed to the Autonomous Government Decentralized of the canton Saraguro and to the agricultural producers of each of the farms considered in the route; Where it was established that the canton has great agricultural and livestock production that can be used for the creation of new tourist alternatives, which could be stimulated by the cantonal AGD through trainings in benefit of its crops and quality of tourist services.